Determination of different social groups' level of knowledge about malaria in a multicultural Amazonian cross-border context - Mélanie Gaillet; Lise Musset; Claire Cropet; Félix Djossou; Adeline Mallard; Guillaume Odonne; Damien Davy; Maylis Douine; Loic Epelboin; Yassamine Lazrek; Luana Mathieu; Mathieu Nacher; et al. (BMC, 2023)
Abstract Background A steady decline in the number of cases of malaria was observed in the 2000s in French Guiana. This enabled regional health policies to shift their public health goal from control to elimination. To include inhabitants in this strategy, the main objective of this study was to describe knowledge about malaria, and related attitudes and practices in persons living in the French Guiana border. Methods We conducted a survey in people over 15 years old living in the twelve neighbourhoods of Saint-Georges de l'Oyapock with the highest malaria incidence. It comprised a 147-item questionnaire which collected data on socio-demographic characteristics and included a Knowledge Attitude and Practices survey on malaria. Knowledge-related data were studied using exploratory statistical methods to derive summary variables. A binary variable assessing level of knowledge was proposed and then assessed using exploratory approaches. Results The mean age of the 844 participants was 37.2 years [15.8], the male/female sex ratio was 0.8. In terms of nationality, 485 (57.5%) participants were Brazilian and 352 (41.7%) French. One third (305, 36.1%) spoke Brazilian Portuguese as their native language, 295 (34.9%) the Amerindian language Palikur, 36 (4.3%) French. The symptoms of malaria and prevention means were poorly known by 213 (25.2%) and 378 (44.8%) respondents, respectively. A quarter (206, 24.4%) did not know that malaria can be fatal. Overall, 251 people (29.7%) had an overall poor level of knowledge about malaria. Being under 25 years old, living in a native Amerindian neighbourhood, having an Amerindian mother tongue language, having risk behaviours related to gold mining were significantly associated with a poor level of knowledge. Conclusions This study is the first to describe the poor level of knowledge about malaria in populations living in the malaria endemic border area along the Oyapock river in French Guiana. Results will allow to reinforce, to diversify and to culturally adapt prevention messages and health promotion to increase their effectiveness with a view to quickly reaching the goal of malaria elimination through empowerment.